Studying paracetamol and aspirin medicine by Raman spectroscopy - Luu, Thi Lan Anh; Nguyen, Ngoc Trung (Old Journal, 2018)
Raman spectral method is non-destructive analysis method, not sample preparation. This technique has recently been used for rapid test and for the detection of counterfeit drugs. In this article, we have used Raman spectral to study paracetamol and aspirin. We have developed five formulas for the preparation of paracetamol and aspirin active ingredients (5%, 10%, 15%, 20%, 25% and 50%) with types of excipient corresponding to 05 formulas. In this work, we also investigated the development of a qualitative analysis process and limited the detection of paracetamol and aspirin. The results can be used to test the quality of drugs in the market.